The Analysis of Transitivity System in Tourism Destination Brochure Based on Systemic Functional Linguistic - Ragiel Yusuf Anando Jasuma; Nur Ijabah (Universitas Muhammadiyah Kalimantan Timur, 2023)
The effectiveness of using language in a brochure is not something that easy to interpret. Information and understanding must be clear and concrete. A good and correct brochure from Systemic Functional Linguistics (SFL) perspective is objectivity that can be understood in terms of appropriate content. The application of SFL in daily activities may simplify the meaning of text sentences so that people could decipher the meaning carefully and minimize misunderstanding the meaning of the related texts. The research was intended to: (1) identify and analyze a transitivity system in the tourism destination brochure of Dinas Kebudayaan, Kepemudaan Olahraga dan Pariwisata Kabupaten Sumenep (2) find out the dominance of the process type in the ideational metafunction in the language used in the brochure. This research was supported by the theory of Halliday and Matthiessen (2004). This study used a qualitative description to develop a research index in terms of analyzing, describing, and agglomerating the existing brochure at the Gili Labak tourism destination, Sumenep, Madura. The results found that transitivity systems have a role to make meanings in a clause and the relational process was the dominant type of process involved in the brochures. This research is expected to be a reference for further research by discussing Systemic Functional Linguistics thus it becomes the data that has solutions for the application of language that parses through processes in ideational metafunction.